Research on 3D reconstruction of late Victorian riding skirts. Issue 6 (5th November 2018) - Kuzmichev, Victor; Moskvin, Aleksei; Moskvina, Mariia; Pryor, Jane
Abstract : Purpose: Virtual design of contemporary and historical clothes is a very intensive and developing area of science that can be considered as a bridge between costume heritage and modern way of its presentation by means of CAD. The purpose of this paper is to apply 2D and 3D existing CAD for virtual reconstruction of the very specific kind of women's clothes such as a side-saddle riding habit (RH) used in 1875–1915. Design/methodology/approach: The construction of RH was adapted to the aesthetic rules of the mentioned time, ergonomic posture of a woman sitting on a horse, surface of the horse's body which the woman is sitting on. For the new method, the huge databases were obtained after analyzing the historical pattern manuals and features of pattern blocks used, possible postures of riding, construction of RH and converting it into virtual system "avatar – RH." To reconstruct the side-saddle RH in virtual reality, the images dated 1887 and authentic pattern blocks were used. Special attention has been given to the topology of contacting areas existing between the sitting woman and "shaped" riding skirt and to the method of presenting it by means of special points combination. Findings: The authors have developed a new method of virtual reconstruction of an RH that is based on automatic consideration of all joining elements such as "shaped" riding skirt, avatar and its ergonomic posture. The new approach allows reconstruction of the clothes in virtual reality in three ways: by using the real skirts, the historical pattern blocks or pictures. Originality/value: The results obtained allow increased possibilities of virtual reconstruction and include in the list new objects of engineering achievements of the nineteenth century such as the side-saddle RH. This study should help researchers and practical specialists to recreate and save the historical treasure in a digital way.